Réponses

  • Omnes
  • Modérateur confirmé
2014-02-28T23:30:59+01:00
Salut,

A =  \frac{10^{2} - 6 * 3^{2}  }{2^{6} - 3 * 4^{2}  } =  \frac{100 - 6 * 9}{64 - 3*16} =  \frac{100-54}{64-48} =  \frac{46}{16} =  \frac{23}{8} \\


B =  \frac{400*10^{-1} - 6 * 10^{2} }{5.6*10^{-3} } \\
B =  \frac{40-600}{5.6*10^{-3} } \\
B =  \frac{-5,6*10^2}{5.6*10^{-3} } = -10^{2-(-3)}= -10^{5} = -100000
C =  \frac{42 * 10 ^{-3} * 5 * (10^{2})^{3}   }{3*10^{6} } \\
C =  \frac{210 * 10^{-3} * 10^{2*3} }{3*10^{6} } \\
C =  \frac{210 * 10^{-3+6} }{3*10^{6} } \\
C =  \frac{210*10^{3} }{3*10^{6}} \\
C= 7*10^{3-6} \\
C = 7 * 10^{-3} = 0.07

Bonne soirée !
Tu es vraiment fort, bravo !
salut les * representent les X ?
les multiplié oui :)
ok merci beaucoup :)